Sarcopenia Is Negatively Related to High Gravitational Impacts Achieved From Day-to-day Physical Activity. (22nd November 2017) - Hartley, April; Gregson, Celia L; Hannam, Kimberly; Deere, Kevin C; Clark, Emma M; Tobias, Jon H
Abstract: Background: Sarcopenia has been associated with reduced physical activity (PA). We aimed to determine if sarcopenia, and specific components of muscle size, function, and physical performance, are associated with high impacts achieved during habitual PA, as these are related to bone strength in community-dwelling older women. Methods: Participants were older women from the Cohort of Skeletal Health in Bristol and Avon. We defined sarcopenia using the EWGSOP criteria. Lower limb peak muscle power and force were assessed using Jumping Mechanography (JM). High vertical impacts were assessed by tri-axial accelerometry (at least 1.5g above gravity). Cross-sectional associations were analyzed by linear regression, adjusting for age, height and weight (or fat mass for models including appendicular lean mass index), comorbidities, smoking, alcohol, and Index of Multiple Deprivation. Results: Our analyses included 380 participants, with mean age 76.7 ( SD 3.0) years; 242 (64%) also completed JM. In age-adjusted analysis, a negative relationship was observed between severity of sarcopenia and high, but not medium or low, impacts ( p = .03 for trend). Regarding components of sarcopenia underlying this relationship, multivariable analyses revealed that gait speed (β 1.47 [95% CI 1.14, 1.89], [β-1] reflects the proportionate increase in high impacts per SD increase in exposure) and peak force (1.40 [1.07, 1.84]) were independently associated with high impacts. Conclusions: Older women with sarcopenia experienced fewer bone-strengthening high impacts than those with presarcopenia or without sarcopenia. To increase bone strengthening activity in older women, interventions need to improve both lower limb muscle force and walking speed.